Pb-Pb ages of feldspathic clasts in two Apollo 14 breccia samples. (15th November 2017) - Nemchin, A.A.; Jeon, H.; Bellucci, J.J.; Timms, N.E.; Snape, J.F.; Kilburn, M.R.; Whitehouse, M.J.
Abstract: Pb-Pb isochron ages of ca. 3.92 Ga for three K-feldspar-rich clasts from Apollo 14 breccias 14303 and 14083 were determined using Secondary Ion Mass Spectrometry (SIMS). These ages are interpreted to represent the resetting of the U-Pb system in the clasts as a result of brecciation during the Imbrium impact. One of the clasts contains zircon grains that record a significantly older crystallization age (ca. 4.33–4.35 Ga) for the rock represented by that clast. Initial Pb compositions determined for the clasts, combined with the previously measured Pb isotopic compositions of K-feldspar grains from several Apollo 14 breccia samples, constrain a range of initial Pb compositions in the ca. 3.9 Ga Fra Mauro formation at the Apollo 14 landing site. This range in initial Pb compositions indicates that the rocks represented by these clasts, or the sources of those rocks, evolved with a high 238 U/ 204 Pb (μ-value) for substantial periods of time, although the precise crystallization ages of the rocks represented by at least two of the clasts investigated here are unknown.